[Farm Complex at Glaumbur] - Streng, Evelyn Fiedler (1975)
Photograph of a farm complex in Glaumbær. White farmhouses covered in sod and grass sit in a line in the grass. A wooden fence covered in wire sits at the bottom of the photograph. Mountains are visible in the background to the left, a road stretching toward the mountain.